HOME ENVIRONMENT AND MOTOR PERFORMANCE OF PRESCHOOLERS - Gislaine Contessoto Pizzo; Guilherme Futoshi Nakashima Amaro; Pamela Norraila da Silva; Nayara Malheiros Caruzzo; José Luiz Lopes Vieira; Patrik Felipe Nazario (Universidade Estadual do Oeste do Paraná, 2014)
The aim of this study was to analyze the relation between home environment and motor performance of children. Twenty-four children aged between 36 to 42 months have participated of this study. The Movement Assessment Battery for Children Second Edition (MABC-2) was used to analyze the motor performance; whereas, the Affordance in the Home Environment for Motor Development Self Report (AHEMD-SR) questionnaire was used to verify the quality of childrens home environment. Data was reported through median and interquartile range, and spearmans rank coefficient was used for correlations between variables. Results have showed low opportunities and stimulation for the motor development of children offered by home environment. However, this did not influence the childrens motor development. It is possible to conclude that for this sample the home environment had no effect on childrens motor development. Nevertheless, it is necessary that parents have better understand of the importance of the home environment and its potential to afford opportunities for childrens development